Chapter - 3, Proofs

Section - 3.5 - Disjunctions


Summary

  • To use a given of the form $P \lor Q$:
    • Break proof into cases. For case 1, assume that $P$ is true and use this assumption to prove the goal. For case 2, assume $Q$ is true and give another proof of the goal.
    • Another strategy can be: If it is also given $\lnot P$, or it can also be proved that $P$is false, then use this given to conclude that Q is true. Similarly, if it is given $\lnot Q$ or it can be proved that $Q$ is false, then it can be used to conclude that $P$ is true.
  • To prove a goal of the form $P ∨ Q$:
    • Break the proof into cases. In each case, either prove P or prove Q.
    • Another strategy can be: If $P$ is true, then clearly the goal $P \lor Q$ is true, so only need to worry about the case in which $P$ is false. Thus for the case $P$ is false, complete the proof by proving that $Q$ is true. Point to note here is this strategy is same as proving the goal $\lnot P \to Q$. Similarly it $Q$ can be used instead of $P$.

Soln1

Suppose $x \in A \cap (B \cup C)$. Thus $x \in A$ and $x \in B \lor x \in C$. Thus we have two cases:

Case 1: Suppose $x \in B$. Since $x \in A$, it follows that $x \in (A \cap B)$. Thus $x \in (A \cap B) \cup C$.

Case 2: Suppose $x \in C$. Thus $x \in (A \cap B) \cup C$.

Thus in all the cases, $x \in (A \cap B) \cup C$. Since $x$ is arbitrary, $A \cap (B \cup C) \subseteq (A \cup B) \cap C$.


Soln2

Suppose $x \in (A \cup B) \setminus C$. Thus either $x \in A \setminus C$ or $x \in B \setminus C$. Thus we have two cases:

Case 1: Suppose $x \in A \setminus C$. Thus $x \in A$. Since $x \in A$, it follows that $x \in ( A \cup (B \setminus C) )$.

Case 2: Suppose $x \in B \setminus C$. Clearly it follows that $x \in ( A \cup (B \setminus C) )$.

Thus in all the possible cases, $x \in ( A \cup (B \setminus C) )$. Since $x$ is arbitrary, we can conclude that $(A \cup B) \; \subseteq \; A \cup (B \setminus C)$.


Soln3

Suppose $x \in (A \setminus (A \setminus B))$. Thus we have:

$x \in A \land \lnot (x \in (A \setminus B))$.
$\quad = x \in A \land \lnot(x \in A \land x \notin B)$.
$\quad = x \in A \land (x \notin A \lor x \in B)$.
$\quad = x \in A \land x \in B$.
$\quad = x \in (A \cap B)$.

Since $x$ is arbitrary, we can conclude that $A \setminus (A \setminus B) = A \cap B$.


Soln4

Suppose A ∩ C ⊆ B ∩ C and A ∪ C ⊆ B ∪ C. Prove that A ⊆ B.

Suppose $x \in A$. Then $x \in A \cup C$. Since $A \cup C \subseteq B \cup C$, it follows that $x \in B \cup C$. Thus either $x \in B$ or, $x \in C$. So we have following cases:

Case 1: Suppose $x \in B$, then it follows $x \in A \to x \in B$.

Case 2: Suppose $x \in C$. Thus $x \in A \land x \in C$. Since $A \cap C \subseteq B \cap C$, it follows that $x \in B$.

Thus from all the cases, if $x \in A$, then $x \in B$. Since $x$ is arbitrary, it follows that $A \subseteq B$.


Soln5

We shall prove this using contra-positive. Suppose $x \notin A$. Since $((A \setminus B) \cup (B \setminus A)) \subseteq A$, it follows that $x \notin ((A \setminus B) \cup (B \setminus A))$. Thus $x \notin (A \setminus B)$ as well as $x \notin (B \setminus A)$. Since $x \notin A$, then clearly $x \notin (A \setminus B)$. Thus we are left with $x \notin (B \setminus A)$. This can be simplified into $\lnot (x \in B \land x \notin A)$ which is equivalent to $x \notin B \lor x \in A$. Since $x \notin A$, and $x \notin B \lor x \in A$, it follows that $x \notin B$. Thus we have if $x \notin A$ then $x \notin B$. By contra-positive, we can say if $x \in B$ then $x \in A$. Since $x$ is arbitrary, we can conclude that $B \subseteq A$.


Soln6

($\to$)Suppose $A \cup C \subseteq B \cup C$. Suppose $x \in A \setminus C$. Thus $x \in A \cup C$. Since $A \cup C \subseteq B \cup C$, it follows that $x \in B \cup C$. And since $x \in B \setminus C$, it follows that $x \in B$. Thus we have $x \in B \land x \notin C$. Since $x$ is arbitrary, we can conclude that $A \setminus C \subseteq B \setminus C$.

($\leftarrow$)Suppose $A \setminus C \subseteq B \setminus C$. Suppose $x \in A \cup C$. Thus we have two cases:

Case 1: Suppose $x \in C$. Then clearly $x \in B \cup C$.

Case 2: Suppose $x \notin C$. Then since $x \in A \cup C$, we have $x \in A$. Thus $x \in A \setminus C$. Since $A \setminus C \subseteq B \setminus C$, it follows that, $x \in (B \setminus C)$. Since $x \notin C$, it follows that $x \in B$. Thus we can say that $x \in (B \cup C)$.

Thus from all the possible cases, if $x \in A \cup C$ then $x \in B \cup C$. Since $x$ is arbitrary, we can conclude that $A \cup C \subseteq B \cup C$.


Soln7

Suppose $x \in \mathcal P(A) \cup \mathcal P(B)$. Thus we have two possible cases:

Case 1: Suppose $x \in \mathcal P(A)$. Then $x \subseteq A$. Suppose $y \in x$, then $y \in A$. Since $y \in A$, then $y \in A \cup B$. Since $y$ is arbitrary, it follows that $x \subseteq (A \cup B)$. Thus we have $x \in \mathcal P(A \cup B)$.

Case 2: Suppose $x \in \mathcal P(B)$. Then $x \subseteq B$. Suppose $y \in x$, then $y \in B$. Since $y \in B$, then $y \in A \cup B$. Since $y$ is arbitrary, it follows that $x \subseteq (A \cup B)$. Thus we have $x \in \mathcal P(A \cup B)$.

Thus from all cases, if $x \in \mathcal P(A) \cup \mathcal P(B)$, then $x \in \mathcal P(A \cup B)$. Since $x$ is arbitrary, it follows that $\mathcal P(A) \cup \mathcal P(B) \subseteq \mathcal P(A \cup B)$.


Soln8

Suppose $\mathcal P(A) \cup \mathcal P(B) = \mathcal P(A \cup B)$. Then $A \cup B \in \mathcal P(A \cup B)$. Since $\mathcal P(A \cup B) = \mathcal P(A) \cup \mathcal P(B)$, it follows that $A \cup B \in \mathcal P(A) \cup \mathcal P(B)$. Thus we have following cases:

Case 1: Suppose $A \cup B \in \mathcal P(A)$. Then $A \cup B \subseteq A$. It follows that $B \subseteq A$.

Case 2: Suppose $A \cup B \in \mathcal P(B)$. Then $A \cup B \subseteq B$. It follows that $B \subseteq B$.

Thus we have either $A \subseteq B$ or $B \subseteq A$.


Soln9

Suppose $y + \frac 1 x = 1 + \frac y x$. It is equivalent to:
$\leftrightarrow \frac {xy + 1} x = \frac {x + y} x$
$\leftrightarrow xy + 1 = x + y$
$\leftrightarrow xy - x - y + 1 = 0$
$\leftrightarrow x(y - 1) - 1(y - 1) = 0$
$\leftrightarrow (x - 1)(y - 1) = 0$
$\leftrightarrow x = 1 \lor y = 1$


Soln10

Suppose $\vert x - 3 \vert > 3$. Then we have two cases:

Case 1: Suppose $x - 3 > 0$. Then $x - 3 > 3$. It follows that $x > 6$. Multiplying both sides by $x$, we get $x^2 > 6x$.

Case 2: Suppose $x - 3 < 0$. Then $3 - x > 3$. It follows that $x < 0$. Since $x < 0$, $x^2 > 0$ and $6x < 0$. Thus $x^2 > 6x$.


Soln11

($\to$)Suppose $\vert 2x - 6 \vert > x$. Then we have two cases:

Case 1: Suppose $2x - 6 > 0$, then $2x - 6 > x$.
$\leftrightarrow x > 6$.
$\leftrightarrow x - 4 > 2$.
Since $x - 4 > 0$, it follows that \vert x - 4 \vert > 2 $$.

Case 2: Suppose $2x - 6 < 0$, then $6 - 2x > x$
$\leftrightarrow 6 > 3x$
$\leftrightarrow x < 2$
$\leftrightarrow x - 4 < -2$
$\leftrightarrow 4 - x > 2$
Since $x - 4 < 0$, it follows that \vert x - 4 \vert > 2.

($\leftarrow$)Suppose $\vert x - 4 \vert > 2$. Then we have two cases:

Case 1: Suppose $x - 4 > 0$, then $x - 4 > 2$.
$\leftrightarrow x > 6$.
$\leftrightarrow x - 6 > 0$.
$\leftrightarrow 2x - 6 > x$.
Since $x > 6$, so $2x - 6 > 0$.
Thus $\vert 2x - 6 \vert > x$.

Case 2: Suppose $x - 4 < 0$, then $4 - x > 2$.
$\leftrightarrow -x > -2$.
$\leftrightarrow x < 2$.
$\leftrightarrow 3x < 6$.
$\leftrightarrow 3x - 6 < 0$.
$\leftrightarrow 2x - 6 < 0 - x$.
$\leftrightarrow 2x - 6 < -x$.
Since $x < 2$, it follows that $2x - 6 < 0$.
And since $2x - 6 < 0$, it follows that $6 - 2x > x$, Or $\vert 2x - 6 \vert > x$.


Soln12

(a)

($\to$)Suppose $\vert a \vert \le b$. Then we have two cases:

Case 1: Suppose $a > 0$, then $a \le b$.

Case 2: Suppose $a < 0$, then $-a \le b$. Or $a \ge -b$.

Thus from both cases, $-b \le a \le b$.

($\leftarrow$)Suppose $-b \le a \le b$. Then we have following possible cases:

Case 1: Suppose $a > 0$, then $\vert a \vert = a$. Since $a \le b$, it follows that $\vert a \vert \le b$.

Case 2: Suppose $a < 0$, then $\vert a \vert = -a$. Since $-b \le a$, or $b \ge -a$, it follows that $b \ge \vert a \vert$.

Thus form both cases, we have $\vert a \vert \le b$.

(b)

First lets prove $x <= \vert x \vert$, because:

  • if $x >= 0$ then $\vert x \vert = x$, thus $x <= \vert x \vert$ is true.
  • if $x < 0$ then $\vert x \vert = x$, thus $x <= -x$ is true, it follows $x <= \vert x \vert$ is true.

Thus we have $x <= \vert x \vert$.

We know that(from (a)), $\vert a \vert \le b \leftrightarrow -b \le a \le b$. Suppose $b = \vert x \vert$ and $a = \vert x \vert$. Since $x <= \vert x \vert$, it follows that, $- \vert x \vert \le x \le \vert x \vert$.

(c)

We have following all possible cases:

  • Case 1: $x \ge 0 \land y \ge 0$.

As $x + y \ge 0$, $\vert x + y \vert = x + y$.

Also since $x \ge 0$, $\vert x \vert = x$.
Similarly since $y \ge 0$, $\vert y \vert = y$.
Thus $\vert x \vert + \vert y \vert = x + y$.

From above we can conclude $\vert x + y \vert = \vert x \vert + \vert y \vert$.

  • Case 2: $x < 0 \land y < 0$.

As $x + y < 0$, $\vert x + y \vert = - (x + y)$.

Also since $x < 0$, $\vert x \vert = -x$.
Similarly since $y < 0$, $\vert y \vert = -y$.
Thus $\vert x \vert + \vert y \vert = -(x + y)$.

We can conclude $\vert x + y \vert = \vert x \vert + \vert y \vert$.

  • Case 3: $x \ge 0 \land y \le 0$: Here we have following further cases:

    • Case a: $x + y >= 0$:
      LHS:
      Since $x + y \ge 0$, $\vert x + y \vert = x + y$.
      As $x + y > 0 \land x >= 0 \land y <= 0$, it follows that $x + y \le x$.
      Thus we have $\vert x + y \vert \le x$.
      RHS:
      Since $x >= 0$, $\vert x \vert = x$.
      Also, since $y <=0$, $\vert y \vert = -y$.
      Thus $\vert x \vert + \vert y \vert = x - y$. Since $x >= 0 \land y <= 0$, it follows $x - y >= x$.
      Thus we have $\vert x \vert + \vert y \vert >= x$
      So,
      we can conclude that $\vert x + y \vert \le \vert x \vert + \vert y \vert$.

    • Case b: $x + y < 0$: LHS:
      Since $x + y < 0$, $\vert x + y \vert = -(x + y)$.
      As $x + y < 0 \land x >= 0 \land y <= 0$, it follows that $(x + y) \ge y$ or $-(x+y) \le y$.
      Thus we have $\vert x + y \vert \le y$.
      RHS:
      Since $x >= 0$, $\vert x \vert = x$.
      Also, since $y <=0$, $\vert y \vert = -y$.
      Thus $\vert x \vert + \vert y \vert = x - y$. Since $x >= 0 \land y <= 0$, it follows $x - y >= y$.
      Thus we have $\vert x \vert + \vert y \vert >= y$
      So,
      we can conclude that $\vert x + y \vert \le \vert x \vert + \vert y \vert$.

  • Case 4: $x \le 0 \land y \ge 0$:
    This case is similar to Case 3. By swapping $x$ and $y$, proof will be same as in Case 3.

Thus from all the cases above: $\vert x + y \vert \le \vert x \vert + \vert y \vert$.


Soln13

Suppose $x$ is an integer. Thus $x$ can either be even or odd. We have following cases:

  • Case 1: $x$ is even. Then $x = 2k$, where $k$ is any integer. Thus $x^2 + x = 4k^2 + 2k = 2(2k^2 + k)$. Since $k$ is integer, it follows that $2k^2 + k$ is also an integer. Thus $2(2k^2 + k)$ is an even integer. Thus we can conclude if $x$ is even, then $x^2 + x$ is also an even integer.

  • Case 2: $x$ is odd. Then $x = 2k + 1$, where $k$ is any integer. Thus $x^2 + x = 4k^2 + 4k + 1 + 2k + 1 = 2(2k^2 + 3k + 1)$. Since $k$ is integer, it follows that $2k^2 + 3k + 1$ is also an integer. Thus $2(2k^2 + 3k + 1)$ is an even integer. Thus we can conclude if $x$ is odd, then $x^2 + x$ is also an even integer.

Thus from both cases, $x^2 + x$ is even integer.


Soln14

Suppose $x$ is an integer. We have following possible cases:

Case 1: $x$ is even, or $x = 2k$ where $k$ is even. $x^4 = 16k^4 = 8 \times 2k^4$. Thus $x^4$ is a multiple of $8$ and remainder is zero.

Case 2: $x$ is odd, or $x = 2k + 1$ where $k$ is odd. $x^4 = 16k^4 + 32k^3 + 24k^2 + 8k + 1= 8 \times (2k^4 + 4k^3 + 3k^2 + k) + 1$. Thus $x^4$ is not a multiple of $8$ and clearly remainder is one.

From both cases above, we can conclude that $x^4$ when divided by $8$, remainder will either be zero or one.


Soln15

(a)

Suppose $x$ is arbitrary element and $x \in \cup ( \mathcal F \cup \mathcal G )$.

$\leftrightarrow \exists P \in (\mathcal F \cup \mathcal G)( x \in P)$.
$\leftrightarrow \exists P (P \in (\mathcal F \cup \mathcal G) \land x \in P)$.
$\leftrightarrow \exists P ((P \in \mathcal F \lor P \in \mathcal G) \land x \in P)$.
$\leftrightarrow \exists P ((P \in \mathcal F \land x \in P) \lor (P \in \mathcal G \land x \in P))$.
$\leftrightarrow \exists P (P \in \mathcal F \land x \in P) \lor \exists P (P \in \mathcal G \land x \in P))$.
$\leftrightarrow x \in \cup \mathcal F \lor x \in \cup \mathcal G$.
$\leftrightarrow x \in (\cup \mathcal F) \cup (\cup \mathcal G)$.

Since $x$ is arbitrary, it follows that $\cup ( \mathcal F \cup \mathcal G ) = (\cup \mathcal F) \cup (\cup \mathcal G)$.

(b)

Suppose $x \in \cap(\mathcal F \cup \mathcal G)$.

$\leftrightarrow \forall P \in \mathcal F \cup \mathcal G (x \in P)$
$\leftrightarrow \forall P (P \in \mathcal F \cup \mathcal G \to x \in P)$
$\leftrightarrow \forall P ((P \in \mathcal F \lor P \in \mathcal G) \to x \in P)$
$\leftrightarrow \forall P (\lnot (P \in \mathcal F \lor P \in \mathcal G) \lor x \in P)$
$\leftrightarrow \forall P ((P \notin \mathcal F \land P \notin \mathcal G) \lor x \in P)$
$\leftrightarrow \forall P ((P \notin \mathcal F \lor x \in P) \land (P \notin \mathcal G \lor x \in P))$
$\leftrightarrow \forall P ((P \in \mathcal F \to x \in P) \land (P \in \mathcal G \to x \in P))$
$\leftrightarrow \forall P (P \in \mathcal F \to x \in P) \land \forall P (P \in \mathcal G \to x \in P)$
$\leftrightarrow x \in \cap \mathcal F \land x \in \cap \mathcal G$
$\leftrightarrow x \in (\cap \mathcal F) \cap (\cap \mathcal G)$

Thus we can conclude, $\cap(\mathcal F \cup \mathcal G) = (\cap \mathcal F) \cap (\cap \mathcal G)$.


Soln16

(a)

($\to$)Suppose $x \in B \cup (\cup \mathcal F)$. Suppose $\mathcal G = \{ B \}$. Now we have two cases:

  • Case 1: $x \in B$. Since $G = \{ B \}$, It follows that $x$ exist in atleast one of the sets of $G$. Or we can also say that $x$ exists in atleast one of the sets of $\mathcal F \cup \mathcal G$. Thus it follows that $x \in \cup (\mathcal F \cup \mathcal G)$, or $x \in \cup (\mathcal F \cup \mathcal \{ B \} )$.

  • Case 2: $x \in \cup \mathcal F$. It follows that $x$ exists in atleast one of the sets of $F$. Or we can also say that $x$ exists in atleast one of the sets of $\mathcal F \cup \mathcal G$. Thus it follows that $x \in \cup (\mathcal F \cup \mathcal G)$, or $x \in \cup (\mathcal F \cup \mathcal \{ B \} )$.

From both cases above, since $x$ is arbitrary, we can conclude: $B \cup (\cup \mathcal F) \subseteq \cup (\mathcal F \cup \{ B \} )$.

($\leftarrow$)Suppose $x \in \cup (\mathcal F \cup \{ B \} )$. It follows that $x$ exists in atleast one of the sets, say $A$, of $\mathcal F \cup \mathcal G$. Thus we have two cases:

  • Case 1: $A \in \mathcal G$. Since $x \in A$ and $\mathcal G$ contains only one set $B$, it follows $A = B$. Thus $x \in B$.

  • Case 2: $A \in \mathcal F$. Thus there exists atleast one set in $\mathcal F$ such that $x \in A$. Thus we can say that $x \in \cup \mathcal F$.

Thus from above cases, we have $x \in B \lor x \in \cup \mathcal F$. Since $x$ is arbitrary we can say that: $\cup (\mathcal F \cup \{ B \} ) \subseteq B \cup (\cup \mathcal F)$.

Thus we can conclude that $B \cup (\cup \mathcal F) = \cup (\mathcal F \cup \{ B \} )$.

(b)

B ∪ (∩F) = ∩A∈F (B ∪ A)

($\to$)Suppose $x \in B \cup (\cap \mathcal F)$. Thus we have following possible cases:

  • Case 1: $x \in B$. Suppose $A \in \mathcal F$. Since $x \in B$, it follows that $x \in A \cup B$. Also since $A$ is arbitrary, it follows that $\forall A \in \mathcal F ( x \in (A \cup B))$. Or $x \in \cap_{A \in \mathcal F}(A \cup B)$.

  • Case 2: $x \in \cap \mathcal F$. Thus $x$ must exist in all the sets of $\mathcal F$. Thus we can also say that $\forall A \in \mathcal F (x \in A)$. Since $\forall A \in \mathcal F (x \in A)$, it follows that $\forall A \in \mathcal F (x \in A \cup B)$ is also true. Thus we can say that $x \in \cap_{A \in \mathcal F}(A \cup B)$.

Thus from both cases, $B \cup (\cap \mathcal F) \; \subseteq \; \cap_{A \in \mathcal F}(A \cup B)$.

($\leftarrow$)Suppose $x \in \cap_{A \in \mathcal F}(A \cup B)$. Thus $x$ must exist in all sets: $A \cup B$ such that $A \in \mathcal F$. It follows following two cases:

Case 1: $x \in B$. Then it follows that $x \in B \cup (\cap \mathcal F)$.

Case 2: $x \in A$. Since $A$ is arbitrary, it means $x$ exists in all the sets of $\mathcal F$. Or $x \in \cap \mathcal F$. It follows that $x \in B \cup (\cap \mathcal F)$.

Thus from both cases, $\cap_{A \in \mathcal F}(A \cup B) \; \subseteq \; B \cup (\cap \mathcal F)$.

Thus from both directions, we can conclude $B \cup (\cap \mathcal F) \; = \; \cap_{A \in \mathcal F}(A \cup B)$.

(c)

Suppose $x \in B \cap (\cap \mathcal F )$. It appears that $x$ belongs to all the sets of $\mathcal F$ as well as $x$ belongs to $B$. Thus it seems to be equivalent to $\cap_{A \in \mathcal F}(A \cap B)$. Lets try to prove it:

($\to$) Suppose $x \in B \cap (\cap \mathcal F )$. Thus $x$ must exist in $B$. Suppose $A \in \mathcal F$. Since $x$ must exist in all the sets of $\mathcal F$, it follows that $x \in A$. Thus we can also say that $x \in A \land x \in B$, or $x \in A \cap B$. Since $A$ is arbitrary, $\forall A \in \mathcal F(x \in (A \cap B))$. It follows that $x \in \cap_{A \in \mathcal F}(A \cap B)$.

($\leftarrow$). Suppose $x \in \cap_{A \in \mathcal F}(A \cap B)$. Since $x \in (A \cap B)$, $x$ must exist in $B$. Also, since $x \in (A \cap B)$,
$x$ must exist in all the sets, $A$, of $\mathcal F$. Thus $x \in B \land x \in \cap \mathcal F$. Or $x \in B \cap (\cap \mathcal F)$.

Thus from both directions we have $B \cap (\cap \mathcal F ) \; = \; \cap_{A \in \mathcal F}(A \cap B)$.


Soln17

Suppose $x \in \cap \mathcal H$. Suppose $A \in \mathcal F$ and suppose $B \in \mathcal G$, then $A \cup B \in \mathcal H$. Thus it follows that $x \in A \cup B$. So we have two cases:

Case 1: $x \in A$. Since $A$ is arbitrary, it follows that $x \in \cap \mathcal F$. Or $x \in (\cap \mathcal F) \cup (\cap \mathcal G)$.

Case 2: $x \in B$. Since $B$ is arbitrary, it follows that $x \in \cap \mathcal G$. Or $x \in (\cap \mathcal F) \cup (\cap \mathcal G)$.

Thus from both cases if $x \in \cap \mathcal H$, then $x \in (\cap \mathcal F) \cup (\cap \mathcal G)$.


Soln18

Suppose $x \in A \triangle B$. Thus we have:

$\leftrightarrow (x \in A \cup B) \land \lnot (x \in A \cap B)$
$\leftrightarrow (x \in A \lor x \in B) \land \lnot (x \in A \land x \in B)$
$\leftrightarrow (x \in A \lor x \in B) \land (x \notin A \lor x \notin B)$
$\leftrightarrow (x \notin B \to x \in A) \land (x \in A \to x \notin B)$

Now since $x$ is arbitrary, we can conclude that $\forall x ( x \in A \triangle B \; \leftrightarrow (x \in A \leftrightarrow x \notin B))$


Soln19

  • ($((A \triangle B) \cap C = \phi) \; \to \; (A \cap C = B \cap C)$):
    Suppose $(A \triangle B) \cap C = \phi$. Now we shall prove $(A \cap C = B \cap C)$ :

    • ($\to$)Suppose $x \in A \cap C$. Thus $x \in A$ and $x \in C$. We will prove by contradiction. Suppose $x \notin B$. Since $x \in A$, it follows that $x \in A \setminus B$. Thus $x \in A \triangle B$. Since $x \in C$, it contradicts the given that $(A \triangle B) \cap C = \phi$. Thus $x \in B$. Now since $x \in C \land x \in B$, it follows that $x \in B \cap C$.
    • ($\leftarrow$)Suppose $x \in B \cap C$. Thus $x \in B$ and $x \in C$. We will prove by contradiction. Suppose $x \notin A$. Since $x \in B$, it follows that $x \in B \setminus A$. Thus $x \in A \triangle B$. Since $x \in C$, it contradicts the given that $(A \triangle B) \cap C = \phi$. Thus $x \in A$. Now since $x \in C \land x \in A$, it follows that $x \in A \cap C$.

    Thus we can conclude that $A \cap C = B \cap C$.

  • ($(A \cap C = B \cap C) \; \to \; ((A \triangle B) \cap C = \phi)$):
    We will prove this by contra-positive. Suppose $(A \triangle B) \cap C \ne \phi$ and lets say $x \in (A \triangle B) \cap C$. Thus $x \in A \triangle B$ and $x \in C$. Since $x \in A \triangle B$, we have following cases:

    • Case 1: If $x \in A \setminus B$, then $x \in A \land x \notin B$. Since $x \in A \land x \in C$, it follows $x \in A \cap C$. Also since $x \notin B$, it follows that $x \notin B \cap C$. Thus $A \cap C \neq B \cap C$.

    • Case 2: If $x \in B \setminus A$, then $x \in B \land x \notin A$. Since $x \in B \land x \in C$, it follows $x \in B \cap C$. Also since $x \notin A$, it follows that $x \notin A \cap C$. Thus $A \cap C \neq B \cap C$.

    Thus we can conclude from contra-positive that $(A \cap C = B \cap C) \; \to \; ((A \triangle B) \cap C = \phi)$.

Thus from both directions, the condition is true. So we can conclude $(A \cap C = B \cap C) \; \leftrightarrow \; ((A \triangle B) \cap C = \phi)$.


Soln20

  • ($((A \triangle B) \subseteq C) \; \to \; (A \cup C = B \cup C)$):
    Suppose $(A \triangle B) \subseteq C$. Now we will prove $A \cup C = B \cup C$ :

    • $A \cup C \to B \cup C$:
      Suppose $x \in A \cup C$. Thus we have two exhaustive cases:

      • Case 1: If $x \in C$, then $x \in B \cup C$.

      • Case 2: if $x \in A \land x \notin C$. Since $(A \triangle B) \subseteq C$, it follows that $x \notin (A \triangle B)$. It follows that $\lnot ((x \in A \land x \notin B) \lor (x \in B \land x \notin A))$
        $\leftrightarrow (\lnot (x \in A \land x \notin B) \land \lnot (x \in B \land x \notin A))$
        $\leftrightarrow (x \notin A \lor x \in B) \land (x \notin B \lor x \in A))$
        Since $x \in A$, then $x \in B$. Thus we can also say that $x \in B \cup C$.

      Thus from both cases above, we can conclude that $(A \cup C) \to (B \cup C)$.

    • $B \cup C \to A \cup C$:
      This proof is will be exactly similar to the proof above for $(A \cup C) \to (B \cup C)$ by just swapping $A$ and $B$.

    Thus from both directions above, we can conclude that if $(A \triangle B) \subseteq C$, then $A \cup C = B \cup C$.

  • ($(A \cup C = B \cup C) \; \to \; ((A \triangle B) \subseteq C)$):
    Suppose $A \cup C = B \cup C$. Suppose $x \in A \triangle B$, or $x \in (A \setminus B) \lor x \in (B \setminus A)$. Thus we have two possible cases:

    • Case 1: if $x \in A \setminus B$, then $x \in A \land x \notin B$. Since $x \in A$, it follows $x \in A \cup C$. And since $x \in A \cup C$, it follows that $x \in B \cup C$. Since $x \notin B$, it follows that $x \in C$.

    • Case 2: if $x \in B \setminus A$, then $x \in B \land x \notin A$. Since $x \in B$, it follows $x \in B \cup C$. And since $x \in B \cup C$, it follows that $x \in A \cup C$. Since $x \notin A$, it follows that $x \in C$.

    Thus from both cases above, it follows that if $x \in A \triangle B$, then $x \in C$. Since $x$ is arbitrary, it follows that $A \triangle B \subseteq C$.

    Thus from both directions above, we can conclude that $((A \triangle B) \subseteq C) \; \leftrightarrow \; (A \cup C = B \cup C)$.


Soln21

  • $(C \subseteq (A \triangle B)) \; \to \; ((C \subseteq A \cup B) \land A \cap B \cap C = \phi)$:
    Suppose $C \subseteq (A \triangle B)$.

    Proof of $C \subseteq A \cup B$:

    Suppose $x \in C$. Since $C \subseteq (A \triangle B)$, it follows that $x \in A \triangle B$. Thus $x \in A \setminus B \lor x \in B \setminus A$. Thus we have two cases:

    • Case 1: if $x \in A \setminus B$, then $x \in A \land x \notin B$. Since $x \in A$, then $x \in A \cup B$.

    • Case 2: if $x \in B \setminus A$, then $x \in B \land x \notin A$. Since $x \in B$, then $x \in A \cup B$.

    Since $x$ is arbitrary, we can conclude from both the cases above that if $C \subseteq A \cup B$.

    Proof of $A \cap B \cap C = \phi$:

    Now, suppose $A \cap B \cap C \ne \phi$. Suppose $x \in A \cap B \cap C$. Since $x \in C$, it follows $x \in A \triangle B$. Thus $x \notin A \cap B$. But it contradicts with assumption that $x \in A \cap B \cap C$. Thus $A \cap B \cap C = \phi$.

  • $(C \subseteq A \cup B) \land A \cap B \cap C = \phi) \; \to \; (C \subseteq (A \triangle B))$: Suppose $((C \subseteq A \cup B) \land A \cap B \cap C = \phi)$. Suppose $x \in C$. Since $C \subseteq A \cup B$, we have following cases:

    • Case 1: if $x \in A$. Since $A \cap B \cap C = \phi$ and $x \in A \land x \in C$, it follows that $x \notin B$. Thus $x \in A \land x \notin B$, or $x \in A \setminus B$. Since $x \in A \setminus B$, it follows $x \in A \triangle B$.

    • Case 2: if $x \in B$. Since $A \cap B \cap C = \phi$ and $x \in B \land x \in C$, it follows that $x \notin A$. Thus $x \in B \land x \notin A$, or $x \in B \setminus A$. Since $x \in B \setminus A$, it follows $x \in A \triangle B$.

    Thus if $x \in C$, then $x \in A \triangle B$. Since $x$ is arbitrary, we can conclude that $C \subseteq (A \triangle B)$.

Thus from both directions above, we can conclude that $(C \subseteq (A \triangle B)) \; \leftrightarrow \; ((C \subseteq A \cup B) \land A \cap B \cap C = \phi)$.


Soln22

(a)

A\C ⊆ (A\B) ∪ (B\C)

Suppose $x \in A \setminus C$. Thus $x \in A \land x \notin C$. Now we have following possible cases:

  • Case 1: $x \notin B$. Since $x \in A \land x \notin B$, it follows $x \in A \setminus B$. Since $x \in A \setminus B$, it follows $x \in (A \setminus B) \cup (B \setminus C)$.

  • Case 2: $x \in B$. Since $x \in B \land x \notin C$, it follows $x \in B \setminus C$. Since $x \in B \setminus C$, it follows $x \in (A \setminus B) \cup (B \setminus C)$.

Thus from both cases above, $A \setminus C \; \subseteq \; (A \setminus B) \cup (B \setminus C)$.

(b)

Suppose $x \in A \triangle C$. Thus $x \in A \setminus C \lor x \in C \setminus A$. Thus we have two cases:

  • Case 1: $x \in A \setminus C$. Using (a), since $x \in A \setminus C$, then $x \in (A \setminus B) \cup (B \setminus C)$.
    Thus we have two cases:

    • Case a: $x \in A \setminus B$, it follows that $x \in (A \triangle B)$, or we can say $x \in (A \triangle B) \cup (B \triangle C)$.

    • Case b: $x \in B \setminus C$, it follows that $x \in (B \triangle C)$, or we can say $x \in (A \triangle B) \cup (B \triangle C)$.

    Thus from both cases, $x \in (A \triangle B) \cup (B \triangle C)$.

  • Case 2: $x \in C \setminus A$. Using (a), since $x \in C \setminus A$, then $x \in (C \setminus B) \cup (B \setminus A)$.
    Thus we have two cases:

    • Case a: $x \in C \setminus B$, it follows that $x \in (C \triangle B)$, or we can say $x \in (A \triangle B) \cup (B \triangle C)$.

    • Case b: $x \in B \setminus A$, it follows that $x \in (B \triangle A)$, or we can say $x \in (A \triangle B) \cup (B \triangle C)$.

    Thus from both cases, $x \in (A \triangle B) \cup (B \triangle C)$.

Thus from both cases above, we have if $x \in A \triangle C$, then $x \in (A \triangle B) \cup (B \triangle C)$.


Soln 23

(a)

Suppose $x \in (A \cup B) \triangle C$. Thus we have following cases:

  • Case 1: $x \in (A \cup B) \setminus C$.
    Thus we have following cases:
    • Case a: $x \in A \land x \notin C$. Thus $x \in A \setminus C$, it follows that $x \in A \triangle C$. Or we can also say that $x \in (A \triangle C) \cup (B \triangle C)$.

    • Case b: $x \in B \land x \notin C$. Thus $x \in B \setminus C$, it follows that $x \in B \triangle C$. Or we can also say that $x \in (A \triangle C) \cup (B \triangle C)$.

  • Case 2: $x \in C \setminus (A \cup B)$.
    Thus $x \in C \land x \notin (A \cup B)$, or $x \in C \land x \notin A \land x \notin B$. Thus $x \in C \setminus A$ and $x \in C \setminus B$. Thus $x \in C \triangle A$ and $x \in C \triangle B$. It follows that $x \in (A \triangle C) \cup (B \triangle C)$.

Thus from both cases above, $(A \cup B) \triangle C \; \subseteq \; (A \triangle C) \cup (B \triangle C)$.

(b)

Lets say $A = \{ 1, 2\} , B = \{2, 3\}, C = \{ 1, 3 \}$.

Then $A \cup B = \{1,2,3\},$ and $(A \cup B) \triangle C = \{2\}$.

And $A \triangle C = \{2,3\}$, and $B \triangle C = \{1,2\}$. Thus $(A \triangle C) \cup (B \triangle C) = \{1,2,3\}$.

We can see that $(A \cup B) \triangle C \; \neq \; (A \triangle C) \cup (B \triangle C)$.


Soln24

(a)

Suppose $x \in (A \triangle C) \cap (B \triangle C)$. It is equivalent to:
$\leftrightarrow (x \in (A \setminus C) \lor x \in (C \setminus A)) \land ((x \in (B \setminus C) \lor x \in (C \setminus B))$

Thus we have ffollowing cases:

Case 1: $x \in (A \setminus C) \land x \in (B \setminus C)$:
Thus $x \in A \land x \in B$ and $x \notin C$, it follows that $x \in (A \cap B) \triangle C$.

Case 2: $x \in (A \setminus C) \land x \in (C \setminus B)$: Here $x \in C \land x \notin C$, which is not possible. Thus this case is not possible.

Case 3: $x \in (C \setminus A) \land x \in (B \setminus C)$: Here also $x \in C \land x \notin C$, which is not possible. Thus this case is not possible.

Case 4: $x \in (C \setminus A) \land x \in (C \setminus B)$: Here $x \in C$ and $x \notin A \land x \notin B$. Or we can say $x \notin (A \cup B)$. Since $x \notin A \cup B$, it follows $x \notin A \cap B$. Thus $x \in C$ and $x \notin (A \cap C)$. It follows that $x \in C \triangle (A \cap B)$.

Thus from all the possible cases, $x \in (A \cap B) \triangle C$.

(b)

Lets say $A = \{ 1, 2\} , B = \{2, 3\}, C = \{ 1, 3 \}$.

Then $(A \triangle C) \cap (B \triangle C) = \{2\}$.
And $(A \cap B) \triangle C = \{1, 2, 3 \}$.


Soln25

We shall prove the conjecture $((A \triangle C) \setminus (B \triangle C)) \; \subseteq \; ((A \setminus B) \triangle C)$.

Suppose $x \in ((A \triangle C) \setminus (B \triangle C))$. It follows that $x \in A \triangle C$ and $x \notin B \triangle C$.

Since $x \notin B \triangle C$, it follows:
$(x \notin B \land x \notin C) \lor (x \in B \land x \in C)$.

Also, since $x \in A \triangle C$, it follows that:
$x \in A \setminus C \lor x \in C \setminus A$.

Thus we have following possible cases:

  • Case 1: $x \in A \setminus C$ and $x \in B \land x \in C$:
    This case is not possible as $x \notin C \land x \in C$ is not possible.

  • Case 2: $x \in C \setminus A$ and $x \in B \land x \in C$:
    Thus $x \in C \land x \notin A \land x \in B$. Since $x \notin A$, it follows: $x \notin A \setminus B$. Further since $x \in C$, it follows $x \in C \setminus (A \setminus B)$. Thus we can also say $x \in (A \setminus B) \triangle C$.

  • Case 3: $x \in A \setminus C$ and $x \notin B \land x \notin C$:
    Thus $x \in A \land x \notin C \land x \notin B$. Since $x \in A \land x \notin B$, it follows: $x \in A \setminus B$. Further since $x \notin C$, it follows: $x \in (A \setminus B) \setminus C$. Thus we can also say $x \in (A \setminus B) \triangle C$.

  • Case 4: $x \in C \setminus A$ and $x \notin B \land x \notin C$:
    This case is also not possible as $x \in C \land x \notin C$ is not possible.

Thus from all the cases above, we can conclude that $((A \triangle C) \setminus (B \triangle C)) \; \subseteq \; ((A \setminus B) \triangle C)$.

However $((A \setminus B) \triangle C) \; \subseteq \; ((A \triangle C) \setminus (B \triangle C))$ is not correct.

One counter example is:
$A = \{1\}, B = \{1\}, C = \{3\}$.
$(A \setminus B) \triangle C = \{3\}$ and $((A \triangle C) \setminus (B \triangle C)) = \phi$.


Soln26

The proof is not correct as the proof actually shows $x > 0 \lor x < 6$. It can be corrected by changing the cases as follows:

  • Case 1. $x − 3 \ge 0$. Then $\vert x − 3 \vert = x − 3$. Plugging this into the assumption that $\vert x − 3 \vert < 3$, we get $x − 3 < 3$, so clearly x < 6. Also, since $x - 3 \ge 0$, it follows $x \ge 3$. Since $x \ge 3$, we can also say $x > 0$. Thus we have $x < 6 \land x > 0$.

  • Case 2. $x − 3 < 0$. Then $\vert x − 3 \vert = 3 − x$, so the assumption $\vert x − 3 \vert < 3$ means that $3−x < 3$. Therefore $3 < 3+x$, so $0 < x$. Also since $x − 3 < 0$, it follows $x < 3$. Or we can also say $x < 6$. Thus it follows that $0 < x \land x < 6$.

Thus from both the cases: $x > 0 \land x < 6$. Thus we can conclude theorem is correct.


Soln27

Proof and theorem both are correct. The goal is of the form of $P \to Q$.

Following strategies are used:

  • To prove goal of the form of $P \to Q$, $P$ is assumed to be correct and then $Q$ is proved.

  • Given is of the form of $P \land Q$. Thus these two are taken as separate givens.

  • One of the given is of the form $\exists x P(x)$. Thus existential instantiation is used.


Soln28

Proof and theorem both are correct. Following strategies are used:

  • Strategy to prove a goal of the form of $\forall x P(x)$.
  • Strategy to prove a goal of the form of $\exists x P(x)$. Existential instantiation is used.
  • The goal is converted into $P \lor Q$ and strategy to prove on case by case basis is used.

Soln29

Suppose $\forall x P(x) \to \exists x Q(x)$. Thus we have:
$\lnot (\forall x P(x)) \lor \exists x Q(x)$
$\exists x \lnot P(x) \lor \exists x Q(x)$
$\exists x (\lnot P(x) \lor Q(x))$
$\exists x ( P(x) \to Q(x))$


Soln30

Proof and theorem both are not correct.

Counter example: $A = \{ 1, 2 \}, B = \{1\}, C = \{2\}$. Thus niether $A \subseteq B$ and nor $A \subseteq C$.

In the proof, both cases are wrong. For eg: In Case 1, $x \in A \to x \in B$ is not true for all the elements of $A$.


Soln31

For any statement $P(x)$, we can have following possible cases:

  • Case 1: P(x) is true for all values of $x$. Or $\forall x P(x)$. Thus we can also say that $\exists x (\lnot P(x) \lor \forall y P(y))$.

  • Case 2: P(x) is false for atleast one value, say $x_0$, of $x$. Or $\lnot P(x_0)$ is true. Thus we can also say $\exists x (\lnot P(x) \lor \forall y P(y))$.

Thus from both the cases, we can conclude that $\exists x (\lnot P(x) \lor \forall y P(y))$.